Facile synthesis and catalytic performance of Co3O4 nanosheets in situ formed on reduced graphene oxide modified Ni foam. Issue 40 (2nd October 2017) - Song, Congying; Yin, Xianzhi; Li, Biaopeng; Ye, Ke; Zhu, Kai; Cao, Dianxue; Cheng, Kui; Wang, Guiling
Abstract : A three-dimensional (3D) catalyst electrode of Co3 O4 nanosheets in situ formed on reduced graphene oxide modified Ni foam (Co3 O4 /rGO@Ni foam) for H2 O2 electroreduction is prepared by a two-step hydrothermal method. Abstract : A three-dimensional (3D) catalyst electrode of Co3 O4 nanosheets in situ formed on reduced graphene oxide modified Ni foam (Co3 O4 /rGO@Ni foam) for H2 O2 electroreduction is prepared by a two-step hydrothermal method. In the first step, graphene oxide sheets are reduced and formed on the skeleton of Ni foam and Co3 O4 nanosheets are synthesized intermixed with the rGO sheets through the second step. The Co3 O4 nanosheets are made up of plentiful nanoparticles and there are many nanoholes among these nanoparticles which are beneficial for the sufficient contact between H2 O2 and the catalyst. The morphology and phase composition of the Co3 O4 /rGO@Ni foam electrode are studied by X-ray diffraction (XRD), scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The electrocatalytic activity of the as-prepared electrode is investigated by cyclic voltammetry (CV) and chronoamperometry (CA). From the results, it can be seen that in 2 mol L −1 NaOH and 0.5 mol L −1 H2 O2, the reduction current density of H2 O2 on the Co3 O4 /rGO@Ni foam electrode is 450 mA cm −2 at −0.8 V which is much higher than that on Co3 O4 directly supported on Ni foam. This obvious increase of the current density can be attributed to the increase of the surface area of the electrode after the addition of rGO. Also, the interpenetration of rGO and Co3 O4 nanosheets improves the electron and ion transport ability of the electrode which leads to a good electrocatalytic activity and stability of the Co3 O4 /rGO@Ni foam electrode.